Partial properties of ready-to-use shrimp paste affected by heating time - Baiq Rien Handayani; Bambang Dipokusumo; Wiharyani Werdiningsih; Sitta Fitri Rahmadhina (Institut Teknologi Bandung, 2020)
Ready-to-use shrimp paste is a traditional shrimp paste produced by a small producer scale in East Lombok through the non-fermentation process and continued by un-control heating time. The qualities were ununiform. Aim of this study was to determine the physical, sensory and microbial quality of ready-to-use shrimp paste affected by heating time. The method conducted was a completely randomized design. The heating time was arranged for 0 to 70 min, with a 10 min interval. The data was analyzed using Co-Stat Software at 95% significant level, then further tested for significance difference data with Tukey’s HSD. Microbial data was analyzed using descriptive method. The result showed that the properties of ready-to-use shrimp paste were influenced by heating time of controlled oven. The heating time affected moisture content, oHue, sensory of aroma, taste and texture. However, it did not affect the appearance and L value (brightness). Heating time for 50 min at 100oC using the controlled oven is recommended as the best treatment to produce ready-to-use shrimp paste with 32.61% of moisture content, 3.9 x 103 CFU/g of total microbe, less than 102 CFU/g of total fungi and undetected coliform. The shrimp paste had yellow-red color, clean appearance which was specific shrimp paste, very specific odor and taste. It also has a compact texture. Heating time for 50 min at 100oC can extend the shelf life of ready-to-use shrimp paste up to minimum 60 days at room temperature.